THE PROBLEM OF THE CONTINUITY OF THE HUMAN BODY (BEING) AND SOUL, THE PROBLEM OF HUMAN IDENTITY (LUST) IN THE LEGACY OF HAKIM TERMIZI. (Scientific journal of the Fergana State University, 2024)
This article analyzes the question of the views of our great compatriot Hakim at-Termizi on the problem of the inseparability of the human body (being) and spirit, human identity (nafs) in his scientific heritage. It also contains information about key concepts that occupy a special place in the moral views of Sufi scholars.